844. High Risk Behaviors, Suboptimal HIV Viral Suppression, and Limited PrEP Use among People Who Engage in Transactional Sex. (4th December 2021) - Cover, Amelia; Bijole, Phyllis; Eyasu, Rahwa; Ebah, Emade; Ogbumbadiugha-Weekes, Onyinyechi; Mount, Julia; Stevens, Jasmine; Gannon, Catherine; Davis, Ashley; Gayle, Britt; Jones, Miriam; Kier, Randy; et al.
Abstract: Background: In the United States, high rates of HIV transmission persist, particularly due to sexual transmission in marginalized populations. Transactional sex (TS) is a known risk factor for HIV transmission, yet risk behaviors and engagement in HIV treatment and prevention among those who have TS are poorly understood. Methods: GRAVITY is cross-sectional investigation of people living with HIV (PLWH) or HCV in Washington, DC and Baltimore, MD. Epidemiologic survey data were collected at a single timepoint. Patients who endorsed previous year sex in exchange for drugs, money, or shelter were considered positive for TS. Fisher's exact test was used for statistical analysis. Results: Of 500 participants, 81(16%) endorsed TS, the majority of whom were HIV+ (51, 63%) and used drugs daily or more (57, 70%; see Table 1). PLWH with TS were more likely to be Black (44, 86%, p= 0.05) and Trans female (17, 33%, p<0.01) than HIV- participants with TS. In the TS cohort, PLWH were more likely to engage in anal sex (38, 75%, p< 0.01), have sex weekly or more (46, 90%; p< 0.01), have sex with more than 2 partners (27, 77%, p=0.03), and have a history of syphilis (14, 27% p= 0.04) compared to HIV- participants. Only 21% and 35% of PLWH and 17% and 22% of HIV- always used condoms in vaginal sex and anal sex, respectively (p >0.05). Though 41 (80%) PLWH took ART, only 19 (41%) reported viral suppression. Of HIV- participants, 59% had interest in starting Pre-Exposure Prophylaxis (PrEP), but few had been offered (3, 10%), or ever taken PrEP (2, 7%). Table 1: Participant Characteristics and Associations with Transactional Sex and HIV Status Conclusion: In this cohort of people with TS, there were high rates of HIV and racial, sexual, and gender minorities. Notably, PLWH had higher rates of frequent sex, multiple partners, and anal sex, as well as suboptimal viral suppression and condom use during anal sex. As such, PLWH +TS may be a consequential part of HIV transmission networks. While those without HIV also had frequent sex and suboptimal condom use, PrEP experience was limited. As the majority had interest in PrEP, targeted strategies to initiate and maintain PrEP in people with TS may be critical in preventing HIV acquisition. Interventions to identify TS, address high-risk behaviors, achieve and maintain viral suppression amongst +TS PLWH, and connect +TS HIV- individuals to PrEP are key to a comprehensive strategy to end the HIV epidemic. Disclosures: Sarah Kattakuzhy, MD, Gilead Sciences (Scientific Research Study Investigator, Research Grant or Support) Elana S. Rosenthal, MD, Gilead Sciences (Research Grant or Support)Merck (Research Grant or Support)